IMPLEMENTASI KEBIJAKAN PENGELOLAAN SAMPAH KOTA SEMARANG MENURUT PERDA NOMOR 6 TAHUN 2012 TENTANG PENGELOLAAN SAMPAH - Gusrini Yulistia; Margaretha Suryaningsih; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Waste management policy based on the event by the high number of heaps of garbage that exists in the city of Semarang. Production of garbage in the city of Semarang per day reached 800 tons/day with a capacity of landfill of 400 tons/day. This happens because with the increase of the population of Semarang city around 1.5 million inhabitants and is also one of the goals of the urbanization. As a result of such activities is the increased production of waste caused by the people. To deal with the problem of local government issued regulation Semarang city waste management areas number 6 in 2012 about waste management that aims to improve public health and the quality of the environment as well as made the waste as a resource. The purpose of this research is to find out how the implementation and the factors that encourage and inhibit the implementation of waste management Policies according to the Semarang area number 6 in 2012. Research methods used in this research is qualitative research methods are descriptive, i.e. by providing a comprehensive overview of the focus of the research. The results of this research show that the implementation of waste management policies are not fully managed to reduce the number of existing middens. In practice there are still various obstacles such as, communications, resources, disposition and bureaucratic structure. Recommendations that can be given to the problem of socialization such as local regulations through electronic media, the addition of human resources and facility cleanliness, training, motivation for employees as well as the establishment of a special section dealing with communities who break the rules are already set.